Ressuscitação cardiopulmonar pré-hospitalar: fatores determinantes da sobrevida - Daniela Aparecida Morais (2012)
Cardiovascular diseases are the most important group of causes of death in the country, and among these stand out the ischemic heart, responsible for most cases of cardiac arrest. Approximately 80.0% of these occur in the prehospital environment. Numerous factors pre and intra-hospital could influence the results of patient care. The aim of this study was to analyze the determinants of patient discharged aliveamong those who received cardiopulmonary resuscitation in the prehospital environment. This was a longitudinal study, carried out with 1165 records of prehospital care of people who received cardiopulmonary resuscitation by teams of Advanced Support Units of Mobile Emergency Care Service in Belo Horizonte, from 01/01/2008 to 17/10/2010. The statistical analysis was made using descriptivestatistics and association measures. It was found that most people (685, or 58.9%) were male, median age was 64 years. The ambulance was used mainly in the morning (342, or 37.1%) and the median time of its displacement was 9 minutes. The return of spontaneous circulation was verified in 239 (20.5%) patients, those were referred to hospitals. That outcome was associated with the "PCR witnessed by people trained in basic life support (OR=3,49; p<0,05; 95%CI), the "PCR attended by SAMU teams (OR=2,99; p<0,05; 95%CI), "the carry out basic life support(OR=0,14; p<0,05; 95%CI), "the initial cardiac rhythm of asystole" (OR=0,33; p<0,05; CI95%). In the hospital, was possible to evaluate 111 (68.5%) records. Most patients (106, or 95.5%) were admitted to the emergency room, 21 (23.6%) had a new PCR on admission and 10 (47.6%) of these died. Were discharged alive 14 patients and factors associated with this outcome were the "spontaneous ventilation within 72hours" and the "sedation." It was possible to visit 11 (91.6%) patients who stayed aware, being independent in activities of daily living. Only one patient did not perform working activities and another had a small memory deficit. The results showed the importance of implementing appropriate care in the prehospital environment and in the hospital; because, even though cardiac arrest is the most serious medicalemergency with worse prognosis in our ambient, there is a possibility that patients recover and return to their normal activities.